Activation of Prostaglandin E Receptor 4 Triggers Secretion of Gut Hormone Peptides GLP-1, GLP-2, and PYY - Coskun, Tamer; O’Farrell, Libbey S.; Syed, Samreen K.; Briere, Daniel A.; Beavers, Lisa S.; DuBois, Susan L.; Michael, Mervyn D.; Franciskovich, Jeffry B.; Barrett, David G.; Efanov, Alexander M. (Endocrinology (Philadelphia), 2013)
Prostaglandins E1 and E2 are synthesized in the intestine and mediate a range of gastrointestinal functions via activation of the prostanoid E type (EP) family of receptors. We examined the potential role of EP receptors in the regulation of gut hormone secretion from L cells. Analysis of mRNA expression in mouse enteroendocrine GLUTag cells demonstrated the abundant expression of EP4 receptor, whereas expression of other EP receptors was much lower. Prostaglandin E1 and E2, nonselective agonists for all EP receptor subtypes, triggered glucagon like peptide 1 (GLP-1) secretion from GLUTag cells, as did the EP4-selective agonists CAY10580 and TCS2510. The effect of EP4 agonists on GLP-1 secretion was blocked by incubation of cells with the EP4-selective antagonist L161,982 or by down-regulating EP4 expression with specific small interfering RNA. Regulation of gut hormone secretion with EP4 agonists was further studied in mice. Administration of EP4 agonists to mice produced a significant elevation of plasma levels of GLP-1, glucagon like peptide 2 (GLP-2) and peptide YY (PYY), whereas gastric inhibitory peptide (GIP) levels were not increased. Thus, our data demonstrate that activation of the EP4 receptor in enteroendocrine L cells triggers secretion of gut hormones.